The Diagnostic Value of Conventional MRI Combined With Diffusion‐Weighted Imaging in Microprolactinomas - Wang, Min‐Yang; Yu, Ying; Han, Yu; Yang, Yang; Jiang, Wan; Liu, Jin; Yan, Lin‐Feng; Cui, Guang‐Bin (Journal of magnetic resonance imaging, 2025)
Background Turbo spin‐echo (TSE) diffusion‐weighted imaging (DWI) sequences may reduce susceptibility artifacts and image distortion in sellar region, allowing better visualization of small pituitary lesions, and may be used to assist in the diagnosis of pituitary microadenomas. Purpose To explore the application value of conventional MRI combined with DWI sequences in the diagnosis of microprolactinomas. Study Type Prospective. Population Thirty‐four patients in microprolactinomas with high signal on T2WI (HT2‐PRL) group (34 females, 34 ± 7 years), 26 patients in microprolactinomas with equal or low signal on T2WI (ELT2‐PRL) group (21 females, 34 ± 7 years), 35 patients with hyperprolactinemia (33 females, 32 ± 8 years), and 30 normal controls (25 females, 31 ± 7 years). Field Strength/Sequence TSE sequence at 3 T. Assessment Pituitary morphological parameters (such as length and volume), dynamic contrast‐enhanced parameters (such as time to peak) and the apparent diffusion coefficients (ADCs) were measured in each group. Statistical Tests ANOVA and Mann–Whitney U test were used to compare parameters among groups. Spearman's coefficient was used to evaluate the correlation between variables. ROC analysis was used to assess the performance of the parameters. A P‐value <0.05 was considered statistically significant. Results The pituitary volume of patients in HT2‐PRL, ELT2‐PRL, and hyperprolactinemia group were 831.00 (747.60, 887.60), 923.63 ± 219.34, and 737.20 (606.40, 836.80) mm3. The pituitary maximum height in these three groups were 7.03 (6.43, 8.63), 8.03 ± 1.41, and 6.63 ± 1.28 mm, respectively. The lesion ADC value was significantly correlated with T2 relative signal intensity (the ratio of signal intensity of microprolactinoma or anterior pituitary to left temporal cortex) (r = 0.821). Compared with patients with hyperprolactinemia, the diagnostic efficacy of T2 relative signal intensity was higher in HT2‐PRL group, with an AUC of 0.954, whereas the ADC value was the highest in ELT2‐PRL group, with an AUC of 0.924. Conclusion DWI sequences can be used to assist in the diagnosis of pituitary microadenomas. Evidence Level 1 Technical Efficacy Stage 2